Methods for ICTs integration - Filippi, José Luis (2008)
New information and communications technologies have hugely contributed to improve the quality of life of society as a whole. They are fully integrated, either as work, study, or game tools or simply as a communication means. Schools – as educational institutions – should include them in their curriculum. This paper presents a contribution to the educational field by proposing the configuration of a method for including ICTs at the basic and the middle levels of the educational system. A self-diagnostics tool indicating usage level of ICTs at schools is proposed, also developing an alerts system that highlights the main weaknesses in the use of ICTs. After the corresponding diagnosis has been carried out, a method is designed for the inclusion of ICTs in institutional spaces. The different integration areas where the ICTs should be included are defined, courses of action are presented, and implementation alternatives are shown.